From pixels to perspectives: exploring perceptions of representation in character design - Tang, Nani Le; Moon, Erin Eungyo; Garrido Iniguez, Jose De Jesus; Ramirez, Daniel Raul Mena; Gardner, Daniel L. (Information Research an international electronic journal, 2025)
Introduction. This study presents findings about perceptions of how women characters are introduced in a sample of six best-selling games. Our analysis adds to ongoing conversations about representation in games and media, encouraging both designers and researchers to reflect on how perceptions and emotions related to representation shape interactions from the perspectives of gamers and non-gamers alike. Method. We analysed 198 responses to a survey that asked participants questions about how they felt about short videos of character introductions and captured open-ended responses about the roles these characters occupied. Analysis. We used descriptive and comparative statistics to identify basic trends in closed-ended survey responses amongst participants. We then identified, applied, and iterated on emergent descriptive qualitative codes designed around participant’s open-ended responses. Results. We identified a series of themes regarding cultural context, perceived characterization and character roles, and time and dialogue. Conclusions. Our findings build on previous literature about character design and women’s representation in games with analysis based on community perceptions and provide considerations for anyone designing characters and their introductions or working with diverse groups to make the medium and industry more inclusive.